STIMULASI KEMAMPUAN BERHITUNG ANAK MELALUI PENDAMPINGAN ORANG TUA SELAMA PANDEMI COVID-19 - Dwi Suryani, Yuni (Jurnal I TIBAR, 2022)
Early childhood is an active individual, has a strong curiosity, is exploratory, and expresses himself spontaneously. During the age range 0-6 years is in the golden age (golden age). The Indonesian government has issued a policy of learning from home activities since the virus that has plagued Covid-19. This restores the role of parents as first and foremost educators for children in family education to guide children. The article is the result of a literature study that aims to find out how to stimulate children's numeracy skills through parental assistance during the COVID-19 pandemic at home. This study examines several reputable published articles, both national and international articles as well as up-to-date books. Based on a review of literature studies, it shows that the parents engagement in developing children's abilities, especially numeracy skills, has a big role. The principle of early childhood learning is play. Therefore, parents take advantage of simple daily activities to develop numeracy concepts such as counting the number of objects in the living room such as chairs, tables, cabinets and at the same time introducing the concept of big-small, far-near, high-low, or counting footsteps when walking into the room, playing cooking (fun cooking) or fishing. Keywords: , ,